Response Surface Methodological Optimization Of Production Condition Of Hyperthermostable Β Amylase From Bacillus Subtilis DJ5 Under Solid State Fermentation Using Barley As Substrate - ABHIJIT PODDAR; TUSHAR KANTI GHARA; SUBHAS CHANDRA JANA (International Journal of Pharma and Bio Sciences, 2012)
Eight different agro-residues were screened for production of hyperthermostable β amylase by Bacillus subtilis DJ5 using SSF. Barley showed highest production of 120.34 U/gdm after 41 hours of incubation. Three process parameters (initial moisture content, pH and incubation temperature) affecting enzyme production under SSF using barley as substrate were optimized with RSM. RSM experiments designed by ‘Stat Ease’ software determined optimum conditions for maximum enzyme production. The best preferred physical conditions were 63.40% initial moisture content, medium pH 6.947 and incubation temperature of 38.50 °C. Under such optimal condition, highest enzyme production of 130.62 U/gdm was recorded after 41 hours of incubation. Incubation temperature was found to play most crucial role for microbial growth and enzyme prodcution under SSF.